Mass Casualty Imaging—Policy, Planning, and Radiology Response to Mass Casualty Incidents. Issue 3 (August 2020) - O'Neill, Siobhán B.; Gibney, Brian; O'Keeffe, Michael E.; Barrett, Sarah; Louis, Luck
A mass casualty incident (MCI) is an event that generates more patients at one time than locally available resources can manage using routine procedures. By their nature, many of these incidents have no prior notice but result in large numbers of casualties with injuries that range in severity. They can happen anywhere and at any time and regional hospitals and health-care providers have to mount a response quickly and effectively to save as many lives as possible. Radiologists must go from passenger to pilot when it comes to MCI planning. When involved at the hospital-wide planning stage, they can offer valuable expertise on how radiology can improve triage accuracy and at what cost in terms of time and resources and thereby contribute a pragmatic understanding of radiology's role and value during MCIs. By taking ownership of MCI planning in their own departments, radiologists can ensure that the radiology department can respond quickly and effectively to unforeseen emergencies. Well-designed radiology protocols will save lives in an MCI setting.